CYBER MEDIA ANALYSIS IN DA'WAH THROUGH MOBILE LEGEND LIVE STREAMING ON YOUTUBE - Kushardiyanti, Dessy; Mutaqin, Zaenal; Nurhidayah, Yayah (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2023)
Da'wah, or Islamic preaching, has expanded into cyber media. This article aims to analyze the use of cyber media for da'wah, focusing on media space, media documentation, and media objects, as exemplified by Ustaz Abi Azkakia's live streaming of Mobile Legends on YouTube. Utilizing a descriptive qualitative approach, the research incorporates literature studies, video documentation, and analysis of media features. The data findings reveal three key aspects: First, the optimization of YouTube as a media space by Ustaz Abi Azkakia for live streaming and uploading da'wah content, including features such as video uploads, shorts, and live streaming. Second, in terms of media documentation, Abi Azkakia effectively engages players by integrating worship and moral values into content, using visually appealing thumbnails, promoting polite behavior, facilitating live chat discussions, and advocating sincere, non-commercial donations. This approach includes personal narratives, stories of the Prophet and his companions, and references to the Al-Qur'an and Hadith. Third, regarding media objects, this article observes an interactivity trend with a modest increase in likes and comments, while the duration of content shows a fluctuating trend, and overall broadcast frequency tends to decrease.